Teachers’ Experiences of Using AI-powered Technologies in Bangladeshi English Language Classrooms - Munni, Benazir Elahee; Rafique, Rumana (Spectrum, 2025)
Artificial Intelligence (AI) tools can potentially revolutionize classroom practices. English as a Foreign Language or Second Language (EFL/ESL) classrooms in higher education (HE) are also privy to the transformative features of AI. However, there is limited research on Bangladeshi HE teachers’ AI usage in teaching. This study, recognizing this gap, investigates Bangladeshi English teachers’ experiences and perceptions of using AI tools at the tertiary-level English classes. Data were collected employing an open-ended qualitative survey distributed among 17 English teachers from various public and private universities in Bangladesh. A thematic analysis suggests that most participants regularly use Turnitin, ChatGPT, and Grammarly among other AI tools. While some teachers did not routinely integrate AI tools into classroom activities, most considered them an efficient auxiliary tool for improving writing, vocabulary, grammar, designing materials, and detecting plagiarism. The results also revealed teachers' concerns about their lack of AI readiness and students’ malpractices using AI such as cheating and disinclination towards critical thinking. Based on the findings, the researchers discovered that effective integration of AI tools in learning can occur through a balance of human-led and AI-led instructions. The study recommended the need for teachers’ capacity building and skills training as mediators for contextually relevant AI usage, predominantly in writing. Spectrum, Volume 18, June 2023: 89-100